[PP.36.25]: ARTERIAL HYPERTENSION AND ASYMPTOMATIC ATRIAL FIBRILLATION IN YOUNG, MIDDLE-AGED AND ELDERLY GROUPS OF BULGARIAN URBAN POPULATION. A CROSS-SECTIONAL STUDY. (June 2015) - Torbova>, S.>; Anev, E.; Yotov, Y.; Tisheva, S.; Ramshev, K.; Ivanova, V.; Kolev, E.
Abstract : Objective: To assess the prevalence of arterial hypertension (AH) and asymptomatic atrial fibrillation (AF) in three age groups – Group 1 - Young (18÷44 yr.), Group 2 - Middle-aged (45÷64 yr.) and Group 3 - Elderly (>65 yr.) in Bulgarian urban population. Design and method: A cross-sectional pilot study was organized on World Hypertension Day (17 may) 2014 by Bulgarian Hypertension League, National Organization of Medical Students and Microlife - Bulgaria. Open – air stands were been organized in 11 Bulgarian cities. Structured questionnaires were filled, blood pressure (BP) was measured by automatic devices with AFIB technology of Microlife for diagnose of atrial fibrillation (AF) without ECG. Voluntary participated 1833 persons (18÷98 yr.), mean age - 59.83 yr. (SD - 16.41); 56% females (F) and 44% males (M). Results: The following prevalence of AH in different age groups was found: Group 1 (mean age - 32.07 yr.) - 18.75%; Group 2 (mean age - 55.82 yr.) - 47.8%; Group 3 (mean age - 73.51 yr.) - 58.9%. The prevalence of newly detected (asymptomatic) AF for all groups was 3.74%, F - 2.55% and M - 5.15 %. The following rates of awareness for AH in persons with newly detected AF within separate age groups were found: Group 1 – Yes- 20%, No - 60%, Don't know - 20%; Group 2 - Yes- 63.64%, No -27.27%, Don't know - 9.09%; Group 3 – Yes- 58.4%, No- 31.70%, Don't know- 9.75%. Regular BP measurement at home was found in: Group 1 - 11.11%, Group 2 - 45.46%, Group 3 - 26.83%. The following incidences of regular antihypertensive treatment in persons with newly detected AF within three groups were found: Group 1 – Yes - 0%; Group 2 – Yes - 77.77%; Group 3 – Yes - 70%. In same persons Diabetes Mellitus was found – Group 1 - 0%, Group 2 - 9.09%, Group 3 - 19.51%. Conclusions: Prevalence of AH and Diabetes Mellitus increases with age, but the prevalence for persons with newly detected AF is higher in middle age group. This group needs more attention.